Resection of Thymic Neuroendocrine Carcinoma Guided by Three-Dimensional Reconstruction: A Case Report - Liu, Fang; Lu, Hengxiao; Chen, Liqian; Geng, Junfeng; Xu, Tongzhen (Frontiers in Medicine, 2022)
Primary thymic small cell neuroendocrine carcinoma (SCNEC), which possesses a more aggressive biological behaviour, including invasion of proximal structures, local recurrence, and distant metastasis, is extremely rare. According to a previous literature report, only a few patients with this disease have been reported, compared to patients with distant metastasis of bones, lungs, spleen, liver, and adrenal glands (1, 2). The report data suggest that SCNEC is a highly malignant tumour compared to most other tumours of the human body. In this study, we presented the case of a patient who underwent surgery guided by three-dimensional reconstruction modelling before the operation. We were fully prepared for the resection of this tumour using three-dimensional reconstruction modelling, even after reading the computed tomography (CT) images that showed a closed relationship with the pericardium, the vein of the right middle lung lobe, and the phrenic nerve. All these features demonstrate that SCNEC is highly malignant. To date, there are no procedural reports for three-dimensional reconstruction modelling in malignant thymus tumours.